2019
DOI: 10.1002/poc.4037
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on optical, electronic, and charge transport properties of star‐shaped benzo[1,2‐b:3,4‐b′:5,6‐b″]trithiophene oligomers

Abstract: We present a study of optical and electronic properties along with reorganization energies in benzo[1,2-b:3,4-b′:5,6-b″]trithiophene (BTT) and its oligomers.The primary objective of this work is to study the effect of the addition of BTT units to the core BTT, on the absorption, electronic, and charge transport properties, using density functional theory (DFT) calculations. The absorption spectra of all molecules were calculated by employing time-dependent DFT (TDDFT) methodology. The results show that the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…From Equation (2), it is clear that the K depends on λ and it is inversely proportional to λ. 29 The hole and electron reorganization energies (λ h and λ e ) can be calculated from Equations (3a) and (3b), [23][24][25][26]30 and the detailed procedure is given in the supporting information S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From Equation (2), it is clear that the K depends on λ and it is inversely proportional to λ. 29 The hole and electron reorganization energies (λ h and λ e ) can be calculated from Equations (3a) and (3b), [23][24][25][26]30 and the detailed procedure is given in the supporting information S1.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular structures of 15 possible isomers of COF (X is O), COTh (X is S), and COSe (X is Se) molecules Also, we have calculated adiabatic and vertical ionization potentials (IP a and IP v ), and adiabatic and vertical electron affinities (EA a and EA v ) as in our previous works. [24][25][26][27]31 RESULTS AND DISCUSSION…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The λ − of L-CG reaches an inorganic-like level as low as 54 meV, which is 2 meV lower than that of representative electron transport material C 60 . 69 The results of Figure 4c showed that the λ + of newly designed CG and L-CG are 38 and 36 meV; 39 and 37 meV; 37 and 35 meV; and 28 and 26 meV smaller than the Deca-BTT, 61 GS-SITF1, 9 GSF1, and GSF2 20 reference molecules, respectively, enlightening that the CG and L-CG could be excellent/ comparable hole transport materials compared to these widebandgap molecules. Figure 4c also shows that values for λ + of CG and L-CG are only 2 and 4 meV as well as 4 and 6 meV higher than the narrow-bandgap benzothiophene 50 and Comp6 67 demonstrating that for the two nanogrids, hole mobility values may be slightly lower/comparable with that displayed by benzothiophene and Comp6.…”
mentioning
confidence: 91%
“…So far, there are four mainstream ways to reduce the ROE, namely, fused cyclization, 51 ladderization, 52−54 macrocyclization, 55−60 as well as star-shaped molecules with an increase in two-dimensional conjugation. 61 However, according to the rough statistics of Liu's group, 50 molecules with small bandgaps have a better chance of obtaining smaller ROEs. While most organic semiconductors have internal ROEs greater than 100 meV, some typical p-type semiconductors such as pentacene and n-type semiconductors such as fullerene (C 60 ) 62 are reported to have ROEs of less than 100 meV.…”
mentioning
confidence: 99%